Synthesis and evaluation of the antiviral activity of 2-(dichloromethyl)pyrazolo[1,5-a][1,3,5]triazines - Velihina, Ye.S.; Pil’o, S.G.; Zyabrev, V.S.; Brovarets, V.S. (Reports of the National Academy of Sciences of Ukraine, 2019)
It is found that N-(2,2-dichloro-1-cyanoethenyl)carboxamides react with 1H-pyrazol-5-amines in the presence of triethylamine to give 2-(dichloromethyl)pyrazolo[1,5-a][1,3,5]triazines. Apparently, this cyclocondensation con sists of the following steps: a) the addition of an NH2 group to the activated C=C bond to form the first amide intermediate, b) the elimination of HCN promoted by triethylamine to give the second amide intermediate, c) the intramolecular cyclization of the latter into the final product with H2O elimination. 2 (Dichloromethyl)-4,7-diphenylpyrazolo[1,5-a] [1,3,5]triazine was stable to boiling MeONa/MeOH, AcONa/AcOH, and Na2S/H2O/EtOH solutions, but cleaved with hydrochloric or sulfuric acid. Five 2-(dichloromethyl)pyrazolo[1,5-a][1,3,5]triazines are tested against i) Dengue virus 2 (strain New Guinea C, cell line Huh7), ii) Tacaribe virus (strain TRVL 11573, cell line Vero), iii) Zika virus (strain MR766, cell line Vero 76), iv) Human cytomegalovirus (strain AD169, cell line HFF), v) Herpes simplex virus 1 (strain E-377, cell line HFF), vi) Varicella-Zoster virus (strain Ellen, cell line HFF). The viral-induced cytopathic effect inhibition, as well as the compound toxicity in host cells, is evaluated. In primary assays (i-iii), the compounds have no sufficient antiviral activity that would exceed their cytotoxicity level at concentrations within 0.1-100 μg/mL, but assays (iv-vi) gave acceptable results. All compounds showed rather a low activity with the exception of 2-(dichloromethyl)-4,7- diphenylpyrazolo[1,5-a][1,3,5]triazine, which, however, had a comparatively high toxicity. In terms of selectivity, the interaction 2-(dichloromethyl)-4,7-bis(4-methylphenyl)pyrazolo[1,5-a][1,3,5]triazine—AD169—HFF (assay iv) with SI50 > 6 is noteworthy.